2005
DOI: 10.1002/jat.1104
|View full text |Cite
|
Sign up to set email alerts
|

Metallothionein induction in the liver, kidney, heart and aorta of cadmium and isoproterenol treated rats

Abstract: Metallothionein (MT), induced in different organs in response to heavy metals and oxidative conditions, exerts antioxidant properties and thus could be implicated in cardiovascular physiopathology. The aim of this study was to investigate the capacity of cadmium (Cd) and isoproterenol to induce in vivo MT not only in rat liver and kidneys but also in heart and aorta. Tissue MT levels, catalase (CAT) and glutathione peroxidase (GPX) activities were assayed at different times after Cd or isoproterenol injection.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 39 publications
(52 reference statements)
0
9
0
1
Order By: Relevance
“…While we did not observe MT staining in the glomerulus, others have reported upregulated MT-I mRNA levels at this site in response to oxidative stress [30]. Beyond a role in zinc excretion, zinc-containing MT at these sites may also be important for oxidative protection, as several authors have shown that MT protects against cadmium-, copper-, mercury-, iron-or isoproterenol-induced renal damage [16,29,[31][32][33][34][35][36] and more specifically against proximal convoluted tubular damage [29,35], agreeing with MT localization in the current study. Also, in a mouse model of diabetic nephropathy, those cross-bred with MT-transgenic mice had delayed progression of renal disease that included tubulointerstitial fibrosis [12], further defining a protective role of MT on tubular pathology.…”
Section: Article In Pressmentioning
confidence: 63%
“…While we did not observe MT staining in the glomerulus, others have reported upregulated MT-I mRNA levels at this site in response to oxidative stress [30]. Beyond a role in zinc excretion, zinc-containing MT at these sites may also be important for oxidative protection, as several authors have shown that MT protects against cadmium-, copper-, mercury-, iron-or isoproterenol-induced renal damage [16,29,[31][32][33][34][35][36] and more specifically against proximal convoluted tubular damage [29,35], agreeing with MT localization in the current study. Also, in a mouse model of diabetic nephropathy, those cross-bred with MT-transgenic mice had delayed progression of renal disease that included tubulointerstitial fibrosis [12], further defining a protective role of MT on tubular pathology.…”
Section: Article In Pressmentioning
confidence: 63%
“…The other study showed that urinary Cd excretion and MT concentrations in kidney were significantly increased in rats exposed to 500 ppm Cd in drinking water for 20 weeks (Kim et al, 2003a). MT content was increased in several tissues (liver, kidney, heart and lung) in different species upon time-dependent Cd exposure (Bobillier-Chaumont et al, 2006; Bonda et al, 2004; Lange et al, 2002). …”
Section: Discussionmentioning
confidence: 99%
“…Increased cardiac MT-I expression is seen in mice in response to streptozocin-induced diabetic cardiomyopathy and in rats in response to cadmium or isoproterenol-induced cardiac injury (9,41). In the silencing of MT expression with a small interfering mRNA, this cardioprotective response is selectively abolished (51).…”
Section: Discussionmentioning
confidence: 99%